Assessment and Analysis of Medication Errors in the Outpatient Pharmacies of a Private Hospital in Batam - Oktaviani, Fifin; Candra, Heldi (Formosa Journal of Science and Technology, 2024)
Medication errors are defined as any preventable event that may cause or result in inappropriate medication use or patient harm when the medication is under the control of a healthcare professional, patient or consumer. Medication errors occur when weak medication systems and/or human factors such as fatigue, poor environmental conditions or understaffing affect prescribing, transcription, dispensing, administration and monitoring practices, which can then result in serious harm, disability and even death. The purpose of this study was to evaluate medication errors in outpatients at a private hospital in Batam City. This study is a cross-sectional study with a retrospective data collection technique from outpatient prescription data in January - March 2022 at a private hospital in Batam City. The sample calculation used the Slovin method with 225 samples. The results of the study stated that the incidence of medication errors at the prescribing stage was 58 (37.7%) unreadable prescriptions, 20 (13%) incorrect doses and 5 (3.2%) inappropriate indications, at the transcription stage there were 11 (7.1%) unexpected drug reaction errors, 34 (22%) errors due to drug interactions, at the dispensing stage there were 22 (14.3%) errors in prescribing dosage forms, 2 (1.3%) due to incorrect manufacturing and preparation and 1 (0.6%) due to incorrect administration of damaged drugs. At the administration stage there were 1 (0.6%) errors due to negligence in giving drugs to patients.